THE INFLUENCE OF MERCHANDISE QUALITY, SERVICE QUALITY, AND STORE SATISFACTION TOWARD STORE LOYALTY ON RETAIL INDUSTRY (A STUDY CASE OF A FOREIGN-OWNED HYPERMARKET IN JAKARTA, INDONESIA) (Jurnal Manajemen, 2015)
This paper investigates the influence of Merchandise Quality, Service Quality and Store Satisfaction toward Store Loyalty in one of foreign-owned hypermarkets in Indonesia. Customer loyalty at the store level is called Store Loyalty, the willingness of customer to repeat purchase at the same store. There are many drivers of customer to be store loyal, such as Merchandise Quality, Service Quality and Store Satisfaction. This research utilizes quantitative research method with binary logistic regression analysis to analyze the data collected from questionnaires spread to 200 respondents as the sample size. The result of this research shows that there is a significant influence of Merchandise Quality, Service Quality, and Store Satisfaction toward Store Loyalty. The biggest influence to Store Loyalty is Store Satisfaction. Â Abstrak Keywords:Â  Merchandise Quality, Service Quality, Store Satisfaction, Store Loyalty